An Epigenetic Memory of Pregnancy in the Mouse Mammary Gland - Camila O. dos Santos; Egor Dolzhenko; Emily Hodges; Andrew D. Smith; Gregory J. Hannon (Cell Reports, 2015)
Pregnancy is the major modulator of mammary gland activity. It induces a tremendous expansion of the mammary epithelium and the generation of alveolar structures for milk production. Anecdotal evidence from multiparous humans indicates that the mammary gland may react less strongly to the first pregnancy than it does to subsequent pregnancies. Here, we verify that the mouse mammary gland responds more robustly to a second pregnancy, indicating that the gland retains a long-term memory of pregnancy. A comparison of genome-wide profiles of DNA methylation in isolated mammary cell types reveals substantial and long-lasting alterations. Since these alterations are maintained in the absence of the signal that induced them, we term them epigenetic. The majority of alterations in DNA methylation affect sites occupied by the Stat5a transcription factor and mark specific genes that are upregulated during pregnancy. We postulate that the epigenetic memory of a first pregnancy primes the activation of gene expression networks that promote mammary gland function in subsequent reproductive cycles. More broadly, our data indicate that physiological experience can broadly alter epigenetic states, functionally modifying the capacity of the affected cells to respond to later stimulatory events.